(untitled) (Medical Forum Monthly, 2024)
Objective: To access the knowledge, attitude, and practices regarding childhood vaccinations among mothers will be evaluated, as well as factors that determine vaccination compliance and skepticism. Study Design: A Cross-sectional Study Place and Duration of Study: This study was conducted at the Department of Pediatrics, Peoples university of Medical Health Sciences NawabShah from February 2023 to July 2023. Methods: A quantitative approach of descriptive cross-sectional design was used to sample 150 mothers with children less than five years of age. To assess the levels of vaccination knowledge, attitudes and practices an interviewer administered structured questionnaire was used. Quantitative data was described by basic descriptive statistics, and associations were tested with the chi square test. The findings were described using standard deviation (SD) and p values. Results: Out of 150 participants, 120 received vaccines strictly according to the schedule while 30 patients claimed that they received their vaccines later or fewer doses. Knowledge score of mothers was 7.8 (± 1.2). A general positive attitude towards vaccination was depicted in 85% of the respondents. A very close relationship was established between knowledge scores and vaccination compliance (p = 0.02). Lower scores were significantly done by those reporting hesitancy (p < 0.05). Conclusion: This study shows that although the majority of mothers’ adhere to vaccination schedules there is still a lack of knowledge. Awareness campaign, learning through knowledge or health interventions could help remove the ignorance and help people follow the immunization programs.